Estimación de valores hemodinámicos mediante el uso del doppler transcraneal en un grupo de voluntarios habitantes de Cali (Colombia), una ciudad a 995 m sobre el nivel del mar (2015)
Transcranial doppler measures the velocity of blood flow in cerebral arteries and the pulsatility index for each artery. The aim of this study was to determine the hemodynamic behaviour in a city located 995 m above sea level, and its association with gender, age and body mass index. The test was performed by an expert on a group of volunteers with no cerebrovascular disease. The study was performed on 51 volunteers (24 men, mean age 46.2 years, and 27 women, mean age: 48.5 years, standard deviation 6.2 years). There were insufficient readings in 6 participants due to an inadequate acoustic window. Statistical differences (P<.01) in the arteries of the left region of the middle cerebral arteries (P<.01), anterior cerebral (P<.1), and extracranial internal carotid (P<.01) suggest the need for gender differentiation among participants.